PARENTâ€™S AND TEACHERâ€™S VIEW OF GENDER STEREOTYPE - Windiarti, Rina (BELIA: Early Childhood Education Papers, 2014)
The role of parents and teachers in changing gender stereotype may a new discussion in Indonesia. The socialication still limiited, thus this topic help inform public about the development, improvement, and how to change gender stereotype in early childhood. This study aimed to explore parentsâ€™ and teachersâ€™ experiences, perceptions, and expectations regarding prevention and management of early childhood gender. The assessment can be done by each thing related to children at home or school e.g. toys, jobs, etc. Need times to socialize and overcome the stereotype for parents, teacher, and also the community around the children. This is necesarryÂ  for the development of the children to allow them thinking â€œout of the boxâ€.